First Report of Sabella spallanzanii (Gmelin, 1791) (Annelida: Polychaeta) from Botany Bay, New South Wales, a northern range extension for the invasive species within Australia - Murray, Anna; Keable, Stephen J. (Zootaxa, 2013)
The European Fanworm, Sabella spallanzanii (Gmelin, 1791), is a known invasive species in Australian coastal waters (Global Invasive Species Database 2013) and has been listed as: